THE BENEFITS OF MUSA PARADISIACA L. (SABA BANANA) AS A SUNNAH–BASED HEALTH IMPROVEMENT ALTERNATIVE - Wardhani, Annisa Eka Adhitya; Maulidiyah, Ananda Riskiyatul; Wulandari, Putri (International Islamic Medicine Forum, 2024)
One of the plants that can be used as the main ingredient of medicine is the banana plant. Basically, the saba banana plant is not only to fulfill daily needs, but can be used as an alternative sunnah-style treatment for physical and spiritual health. Every part of the banana can be used as a source of traditional medicine with easy processing to be practiced daily. Almost all parts of saba banana, starting from the fruit, skin, heart, stem, to the leaves, have different properties such as traditional medicine and industrial raw materials. That way, saba banana can be used as evidence of how blessed Allah SWT's creation has a variety of benefits for humans. Utilizing saba banana as a sunnah-based health improvement alternative is an environmentally friendly step. In addition, saba bananas are also easy to find and affordable and can be consumed every day and are also recommended by scholars as in HR. Tirmidzi.